Simulation of the turbulent air flow of inhalation and exhalation in the respiratory system using computational fluid dynamics - Dheyaa J. Jasim; Mustafa Habeeb Chyad; Laith S. Sabri; Soheil Salahshour; Omid Ali Akbari; M. Hekmatifar (International Journal of Thermofluids)
In this research, the CFD simulation of the respiratory tract was discussed. Limited research was conducted in the field of respiratory systems to examine the respiratory system as a true model for various input structures in inhalation and exhalation, although numerous studies were conducted by researchers. This study aimed to develop a dependable method for obtaining the true respiratory system geometry from a 24-year-old man's CT scan data and preparing it for input into CFD software. this research performs a numerical analysis of the airflow from the nasal inlet in both the inhalation and exhalation modes, using a turbulent airflow mode with a flow rate of 60 liters per minute. The effect of different inputs on the airflow in the human respiratory system is simulated for flat, pipe, and semi-spherical cross sections using CFD for turbulent flow. The results show that the velocity increased as air entered the nasopharynx. In flat, pipe, and semisphere modes, the velocity increased from 2.8 m/s, 2.07 m/s, and 4.14 m/s to 7.41 m/s, 5.48 m/s, and 8.40 m/s, respectively. The Dynamic pressure drop coefficient)Cp(in flat, pipe, and semisphere modes decreased from 79.38, 34.24, and 69.57 to 32.84, 17.13, and 31.44, respectively. The velocity in flat, pipe, and semisphere modes decreased from 7.46 m/s, 4.45 m/s, and 10.29 m/s to 1.54 m/s, 0.96 m/s, and 2.70 m/s, respectively. In the flat and pipe modes, the Cp increased from 17.17, -5.46, to 34.01, and 29.75, respectively. Velocity increased as air entered the larynx. Numerically, the velocity in flat, pipe, and semisphere modes increased from 5.00 m/s, 2.78 m/s, and 7.35 m/s to 9.06 m/s, 6.56 m/s, and 9.79 m/s, respectively. The Cp increased in pipe and semisphere modes. Velocity decreases as the air enters the trachea. Numerically, the velocity in flat, pipe, and semisphere modes decreased from 6.69 m/s, 4.86 m/s, and 7.16 m/s to 3.44 m/s, 3.44 m/s, and 3.90 m/s, respectively. The Cp in the pipe and semisphere modes decreased from 0.77, and -1.59 to -7.33, and -11.51, respectively.